2023
DOI: 10.1111/jsr.13974
|View full text |Cite
|
Sign up to set email alerts
|

Solar clock and school start time effects on adolescents' chronotype and sleep: A review of a gap in the literature

Abstract: SummaryCircadian rhythms are entrained by external factors such as sunlight and social cues, but also depend on internal factors such as age. Adolescents exhibit late chronotypes, but worldwide school starts early in the morning leading to unhealthy sleep habits. Several studies reported that adolescents benefit from later school start times. However, the effect of later school start time on different outcomes varies between studies, and most previous literature only takes into consideration the social clock (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 102 publications
0
1
0
Order By: Relevance
“…Lateness itself, and more importantly, the misalignment between the late endogenous clock and early social pressures (social jet lag, SJL), are considered risk factors for various pathologies such as cardiovascular diseases, metabolic conditions, and addictions [ 3 , 17 , 18 ]. Indeed, recent studies in adolescents have shown that the misalignment, rather than the late chronotype, is the most important factor influencing sleep deficit and academic performance [ [19] , [20] , [21] , [22] ].…”
Section: Introductionmentioning
confidence: 99%
“…Lateness itself, and more importantly, the misalignment between the late endogenous clock and early social pressures (social jet lag, SJL), are considered risk factors for various pathologies such as cardiovascular diseases, metabolic conditions, and addictions [ 3 , 17 , 18 ]. Indeed, recent studies in adolescents have shown that the misalignment, rather than the late chronotype, is the most important factor influencing sleep deficit and academic performance [ [19] , [20] , [21] , [22] ].…”
Section: Introductionmentioning
confidence: 99%